The effect of fiber supplementation on the prevention of diarrhea in hospitalized patients receiving enteral nutrition: A meta-analysis of randomized controlled trials with the GRADE assessment - Kaewdech, Apichat; Sripongpun, Pimsiri; Wetwittayakhlang, Panu; Churuangsuk, Chaitong (Frontiers in Nutrition, 2022)
Introduction Enteral nutrition (EN) in hospitalized patients has several advantages. However, post-feeding diarrhea occurs frequently and has been linked to negative outcomes. The EN formula itself may have an impact on how diarrhea develops, and fiber supplements may theoretically help patients experience less diarrhea. This study aimed to thoroughly evaluate whether adding fiber to EN decreases the likelihood of developing diarrhea and whether different types of fibers pose different effects on diarrhea (PROSPERO CRD 42021279971). Methods We conducted a meta-analysis on fiber supplementation in hospitalized adult patients receiving EN. We thoroughly searched PubMed, Medline, Embase, Scopus, Web of Science, CENTRAL, and ClinicalTrials.gov databases from inception to 1 September 2022. Only randomized controlled trials (RCTs) were included. Pooled results on the incidence of diarrhea were calculated using a random-effects model. The Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach was applied. Only fiber types from soy polysaccharides (n = 4), psyllium (n = 3), mixed soluble/insoluble fiber (mixed fiber, n = 3), pectin (n = 2), and partially hydrolyzed guar gum (PHGG, n = 2) were examined in the sensitivity analysis. Results Among the 4,469 titles found, a total of 16 RCTs were included. Overall, compared to fiber-free formulas, fiber supplementation reduced the occurrence of diarrhea in patients receiving EN by 36% (pooled risk ratio [RR] of 0.64 [95% confidence interval (CI): 0.49–0.82, p = 0.005; I2 = 45%]), with GRADE showing the evidence of moderate certainty. Only mixed fiber and PHGG significantly decreased the incidence of diarrhea according to the sensitivity analyses for fiber types (RR 0.54, 95%CI: 0.39–0.75, I2 = 0% and RR 0.47, 95%CI: 0.27–0.83, I2 = 0%, respectively). The results for the remaining fiber types were unclear. Conclusion According to a meta-analysis, fiber supplements help lessen post-feeding diarrhea in hospitalized patients receiving EN. However, not all fiber types produced successful outcomes. Diarrhea was significantly reduced by PHGG and mixed soluble/insoluble fiber. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=279971, identifier: PROSPERO CRD 42021279971.